Mixing cations and halide anions in perovskite solar cells. (2019) - Gkini, Konstantina E.; Antoniadou, Maria; Balis, Nikolaos; Kaltzoglou, Andreas; Kontos, Athanassios G.; Falaras, Polycarpos
Abstract: In this work we synthesized triple cation (A = Cs, FA, MA), mixed halide (X = I, Br, Cl) APbX3 compounds to develop perovskite solar cells (PSCs) with improved thermal stability as well as high power conversion efficiency. The effects of the cation combination and the mixing of halides in mesostructured PSCs have been thoroughly investigated. The presence of cesium results in greater stability, less impurities and higher reproducibility. Power conversion efficiencies of ∼17% and ∼13.5% were recorded for PSCs with I-Br and I-Cl compounds, respectively. Despite their lower efficiency, the I-Cl containing PSCs exhibit greater stability in ambient conditions.